Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Matematika Dengan Menggunakan Model Pendekatan Matematika Realistik (PMR) Di Kelas V SDN 009 Kebun Tinggi - Ningsih, Fitri (Science and Education Journal (SICEDU), 2024)
The teaching method in the form of lectures used by teachers so far is considered less suitable for use in the classroom because it makes students less involved in the learning process. The aim of this research is to analyze whether the use of the PMR model can improve fifth grade students' learning outcomes regarding Adding Fractions with Different Denominators. . The subjects of this research were 9 students in class V of UPT SDN 009 Kebun Tinggi in the first semester of the 2023/2024 academic year, consisting of 7 male students and 2 female students. The success of this research was observed based on student learning completeness obtained from the scores for each learning improvement cycle. Students are declared to have completed their learning results if they get a score of 62, while a class is declared complete if there are 80% of students who get a score of 62 or more. Based on data obtained in the pre-cycle, of the 9 students who achieved complete learning outcomes, there were 3 students (33.3%). In cycle I there were 5 students (55.5%), while in cycle II there were 8 students (88.8%). By looking at the percentage of student completion in cycle II which exceeds 80% or to be precise (88.8%), the class can be declared complete. So it can be concluded that the learning outcomes of class V students regarding adding fractions with different denominators at UPT SDN 009 Kebun Tinggi are stated to have increased. Therefore, teachers are advised to develop learning using the Realistic Mathematics Approach (PMR) learning model because it can improve student learning outcomes.